Accountability in Public Services in South Africa - World Bank (World Bank, Washington, DC, 2018)
This report discusses selected issues regarding accountability in public services. The introduction discusses the accountability framework that will be used for the report. Chapter 1 assesses South Africa's progress on service access and quality, and summarizes recent policy initiatives. Chapters 2, 3, and 4 describe the international and South African experience with mechanisms that seek to improve accountability - public sector reform, citizen report cards, and others - and posits hypotheses to be explored in the following chapters. Chapter 5 applies the World Bank's accountability framework to a participatory assessment of services in six municipalities in South Africa. Chapters 6 and 7 apply the framework to the education and water and sanitation sectors. Chapter 8 explains why community-driven development does not factor in any main South African development programs. Chapter 9 explains the continuing learning practices pioneered in the manufacturing sector and addresses how these practices might be used by the South African government to effect change. Chapter 10 summarizes the conclusions, translates these into main hypotheses to be tested in future work, and formulates a number of policy recommendations for public debate.